CERVICOTOMY FOR THE MANAGEMENT OF DYSTOCIA DUE TO PREPARTUM VAGINO-CERVICAL PROLAPSE IN COW - RAJA, S; PALANISAMY, M; PRABAHARAN, V; RAJKUMAR, R; JAYAGANTHAN, P (The Indian Journal of Animal Reproduction, 2022)
A case of dystocia due to peripartum vagino-cervical prolapse and imperfect cervical dilatation in a HF crossbred cow and it’s per vaginal delivery by cervicotomy is reported.